2017
DOI: 10.1186/s41029-017-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Action research in Singapore: where are we now?

Abstract: Since the introduction of Learning Circles (a particular model of action research) by the Ministry of Education (MOE) in 2000, action research has grown to become fairly ubiquitous in Singapore education both school-and system-wide in terms of its terminological usage and practice. However, despite its progressive developments over a period of about 15 years, challenges still abound for teachers who seek to enact action research, which range from teachers' heavy workload to the hierarchical work culture. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Considerations of internationally implementation of the results of this research study for other Asian countries, such as Australia (Stamopoulos 2015), the Philippines (Morales 2016) and Singapore (Hairon 2017), an appropriate model of action research in those locations would be the first requirement. This model would be used to support teachers to focus on ongoing self-regulated learning through reflective practice and to sustain the action research model within that country's teacher development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerations of internationally implementation of the results of this research study for other Asian countries, such as Australia (Stamopoulos 2015), the Philippines (Morales 2016) and Singapore (Hairon 2017), an appropriate model of action research in those locations would be the first requirement. This model would be used to support teachers to focus on ongoing self-regulated learning through reflective practice and to sustain the action research model within that country's teacher development.…”
Section: Discussionmentioning
confidence: 99%
“…As another task to sustain teachers' implementation of the action research spiral process in teacher professional development, this study examined way to encourage an additional collaboration of students' parents in the stages of observation and reflection. Research has suggested that in Singapore, the majority of teachers have not been convinced to prioritize professional learning as a responsibility for their teaching life due to great emphasis placed on grading assignments and "giving" student the subject matter content (Hairon 2017). Engaging in an action research approach might be a way to convince those teachers of the importance of professional growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Action research is also acceptable because it encourages teachers to take their own initiative when it comes to the improvement of their teaching in case of encountering certain problems related to teaching and learning. This enables them to explore and test the teaching strategies and thus enhance their professional knowledge (Hairon, 2017). Teachers accept their professional development due to their own conviction that they will consequently enlarge their knowledge and skills, gain specific, particular and practical ideas which will all contribute to their personal advancement and increase their efficiency in teaching (Šteh, Kalin and Mažgon, 2021;Glanz, 2016;Hairon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The role of action research in the system Action research has been promulgated in Singapore by the Ministry of Education since 2000, during the introduction of a teacher collaborative platform called Learning Circles (Hairon, 2017), and has continued to be promoted in Singaporean schools at all levels in the past decade (Soh, 2011). Promotion of action research has resulted from education policymakers' recognition of the need for innovations and improvements in the education system so that the Singaporean workforce can meet its future economic needs.…”
Section: Background On Singapore and Its Education Systemmentioning
confidence: 99%